SURVEI PRAKTEK AKREDITASI LEMBAGA PENDIDIKAN KEJURUAN DAN TEKNOLOGI(VIET) DI NEGARA ANGGOTA ASEAN - Sukardi Sukardi (Universitas Negeri Yogyakarta, 2000)
Syney prqctice of WET accreditation in SHMEO member Countries lnd threb major objectives. These objectives were: l) to prwide information -in ionnection with accreditation; 2) tofacilitate information base - WET instinition for developins other relevant research; j) to enhanbe the Center's'program in frnduc_ ting ap4lild rgsegrch in WET areas. The'sttidy Used survey approach in whlch reiatgd data were gathered with research question as-gltide oJstudy. The questionnoive center and Jormal -all was developed-bi the docamentation was used to pather